PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI PADA KELURAHAN PETAMANAN - -, Rodhiatun Nafisah (JURNAL KINDAI, 2024)
This research aims to analyze the influence of organizational culture and organizational commitment on employee performance. Organizational culture and organizational commitment are considered key factors that influence employee behavior and productivity in an organization. Theoretical approaches and empirical research are used to investigate the relationships between these variables. Furthermore, organizational commitment is explained as the level of employee engagement and desire to actively contribute to achieving organizational goals. Dimensions of commitment, such as affective, normative, and continuative commitment, are analyzed to understand the level of employee engagement. It is hoped that the findings from this research can contribute to the development of human resource management theory and practice. Managerial implications are also discussed to help organizations improve culture and commitment to achieve optimal employee performance. It is hoped that this research will provide a deeper understanding of the internal dynamics of organizations that influence employee performance and provide a basis for further research in this area